THE STUDENTS’ PERFORMANCE IN LISTENING - I Gusti Agung Vony Purnama (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2019)
This study aims to find out the effect of the listening supports on the students’ listening performance. The students under concern were the second-semester students taking the English II subject at STIKOM Bali. The data source in this study is a primary data, which has been got directly from one class of listening comprehension in semester II year in 2017. This class was chosen since the students of this class have already learned the listening comprehension for seven meetings. Theory of listening comprehension was used in this research. There were 34 students’ listening test results analyzed by using the qualitative method in collecting data. This research used a descriptive research in describing the result. The finding shows that the percentage of students’ performance in Listening Comprehension I which used the two listening supports prior the test was 55.2%, this was higher than the percentage of the students’ performance in Listening Comprehension II which did not use the two listening supports only 48.5%. It can be concluded that the two listening supports prior the listening test affect the students listening test result.